Cover Picture: 3 D Imaging and Structural Analysis of a Mesoporous‐Silica‐Body‐Supported Eggshell Cobalt Catalyst for Fischer–Tropsch Synthesis (ChemCatChem 18/2016). Issue 18 (21st September 2016) - Han, Ting; Li, Xiaopeng; Lin, Chao; Zhang, Haojie; Gao, Peng; Zhao, Yonghui; Du, Fuping; Chen, Yuyun; Sun, Yuhan
Abstract : The Front Cover shows a 3D view of the spatial distribution of active metal phases in a millimeter‐sized porous support. In their Full Paper, T. Han, X. Li et al. employed phase‐contrast X‐ray computed microtomography (X‐ray μCT) to image the 3D structure of the cobalt eggshell catalyst. Based on the critical structure information from X‐ray μCT and other conventional characterization technologies, the Fischer–Tropsch performance of eggshell catalysts was fully understood. Their results provide new insights into the impregnation behavior on the millimeter‐sized porous support and offer novel perspectives toward the rational design of industrial catalysts. More information can be found in the Full Paper by T. Han, X. Li et al. onpage 2920 in Issue 18, 2016 (DOI:10.1002/cctc.201600657 ).